Isolation and screening marine fungi with antimicrobial activity from samples collected in Nha Trang bay, VietNam - Hoai Trinh, Phan Thi; Tien, Phi Quyet; Duy Ngoc, Ngo Thi; Ly, Bui Minh; Thanh Van, Tran Thi (Vietnam Journal of Biotechnology, 2018)
The marine environment is an extremely complex ecosystem and contains a broad spectrum of fungal diversity. Marine fungi have been shown to be tremendous sources for new and biologically active secondary metabolites. The present study aims to isolate and screen antimicrobial properties of 100 fungus strains from different marine sources including seaweeds, soft corals, sponges and sediment collected at Nha Trang Bay, Vietnam. In preliminary experiments, the crude extracts of these fungal isolates with ethyl acetate were screened for their antimicrobial activity against the human microbial pathogens including Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Listeria monocytogenes ATCC 19111, Streptococcus faecalis ATCC 19433 and Candida albicans ATCC 10231 by the disc diffusion method. Among the 100 isolates, 59 strains exhibited antimicrobial activity against at least two tested pathogens, that 57% against S. aureus, 50% against L. monocytogenes, 49% against B. cereus, 45% against S. faecalis, 7% against E. coli, 5% against C. albicans, and only 2% against P. aeruginosa. The present study has revealed the presence of high numbers of marine fungi from Nha Trang waters having antimicrobial properties and they need to be investigated further for natural bioactive products